Approximation of ( ψ, β ) - differentiable functions defined on the real axis by Abel-Рoisson operators - Kharkevych, Yurii I.; Zhyhallo, Tetiana V.; Харкевич, Юрій Іліодорович; Жигалло, Тетяна Василівна (Національна академія наук України, 2005)
We obtain asymptotic equalities for upper bounds of approximations of functions on the classes Cψ β,∞ and Lψ β,1 by Abel–Poisson operators.
Наближення ( ψ, β ) - диференційовних функцій, заданих на дійсній осі оператора Абеля-Пуассона